Pre-Service English Teachers’ Experiences of Peer-Reviewing in L2 Writing - Subekti, Adaninggar Septi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
This case study explored pre-service English teachers’ experiences in peer review activities in second language (L2) writing class through secondary data analysis of the participants’ final reflections and peer review documents. The present study used secondary qualitative document analysis as the method. It used two types of secondary data. The study found that learners were still unconfident in giving feedback on grammar and considered assessing peers’ works objectively tricky. However, conducting peer review compelled them to study independently and facilitated them to realise their mistakes. Learners realised the importance of giving clear and accurate feedback but at times struggled to do so due to limited ability. The findings showing learners’ repeated concerns on grammatical aspects in their reflections whilst the peer review activities also included organisation and coherence aspects may indicate that learners prioritised accuracy more than organisation of ideas. Furthermore, several learners appreciated their peers' feedback regardless of quality as a part of learning. It is suggested that peer reviewing is conducted regularly to facilitate learners to learn from each other and to conduct studies on the extent the peer reviewers’ feedback is used to improve the reviewees’ writing.